MEN’S AND WOMEN’S LANGUAGE: INQUIRIES ABOUT HEALTH IN JORDANIAN ARABIC - Malkawi, Nibal Abd Alkareem; Rababa`hMahmoud Ali (European Scientific Journal, ESJ, 2012)
This paper investigates some of the strategies used by Jordanian men and women to ask about each others’ health. Jordanian women usually inquire more than men about the hearer’s health and about his children’s and relatives’ health simply to establish social contact and to show sincere concern for the well-being of the addressees’ family. There are some situations on which the asker cannot talk about directly especially in mixed-dyads; therefore, he should use some euphemistic terms or use indirect expressions to avoid offence to the askee. For example, the fact that a male asking about a sick female’s health improperly may be considered a social mistake because mentioning a female’s name in front of foreign or marriageable people or mentioning the name of some diseases are taboo; this may cause embarrassment to the speaker and his addressee. Therefore, men tend to use more euphemistic terms due to their wider experience and other’s sensitivity of men’s speech upon using non-euphemistic terms Inquiries about health normally encompass proper forms of address. Women tend to use more relational forms and less formal formulas due to their real sincerity to increase intimacy and rapport with their addressee. Jordanian women use inquiries accompanied with kin terms of address more frequently than men do. They use such terms to address foreign or acquainted people either to express solidarity with the well-acquainted or to increase solidarity with the foreign addressees. Some forms of address are almost sex deictic and non- reciprocal. They are used by old Jordanian women to express intimacy even when the relationship is not intimate. The recipient of the inquiry normally replies "ilHamdu lillaah" (Praise be to Allah) in bad or good conditions. Men don’t usually give a detailed reply about their real conditions; they give a conventional response while women normally give a prolonged answer.